2004
DOI: 10.1159/000075952
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Incidence of Brain and Central Nervous System Tumors in Norway, 1970–1999

Abstract: The aim of this study was to investigate trends in the incidence of childhood and adult brain and central nervous system (CNS) tumors in Norway from 1970 through 1999. In this period, a total of 14,641 patients were diagnosed with a primary benign or malignant neoplasm of the brain and CNS. Age-adjusted incidence rates were reported together with results of loglinear regression and an age-period-cohort model based on the Poisson regression model. In children (<15 years), the proportion of brain and CNS tumors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
42
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 45 publications
10
42
0
3
Order By: Relevance
“…1 In Norway, the rates of central nervous system tumors almost doubled from 1970 to 1999. 33 However, between 1989 and 2003, the increase in primary brain tumors (excluding tumors in meninges, corpus pineale, hypophysis, and cranial nerves) was moderate. 34 The average annual incidence rate was 85.7 per million (95% CI, 83.4-87.9 per million), and the EAPC was 2.3% (95% CI, 1.7-2.9%; P < .001) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1 In Norway, the rates of central nervous system tumors almost doubled from 1970 to 1999. 33 However, between 1989 and 2003, the increase in primary brain tumors (excluding tumors in meninges, corpus pineale, hypophysis, and cranial nerves) was moderate. 34 The average annual incidence rate was 85.7 per million (95% CI, 83.4-87.9 per million), and the EAPC was 2.3% (95% CI, 1.7-2.9%; P < .001) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, our results differ from a study in Norway that found equal proportions of spinal cord and spinal meninges, and a study in Croatia finding that > 1 = 2 of the tumors diagnosed in this population were located in the spinal meninges. 17,18 Possible explanations for these differences may be attributed to small sample size or population differences within the Norway and Croatia data sets. Results from our analyses confirm previous findings of frequencies of histology types and sex differences.…”
Section: Our Analyses Add New Insights Into the Descriptive Epidemiolmentioning
confidence: 99%
“…Primary spinal cord tumors are one of the rarest categories of tumors, representing about 4-16 % of all tumors arising from the central nervous systems (CNS) according to previous reports [1][2][3][4][5][6][7][8][9][10][11][12][13]. Because of variation in population sizes studied and classification of tumors, the frequencies of different spinal cord tumors vary among these reports.…”
Section: Introductionmentioning
confidence: 99%